Mobile learning a handbook for developers, educators, and learners - McQuiggan, Scott; Kosturko, Lucy; McQuiggan, Jaime; Sabourin, Jennifer (Hoboken, New Jersey John Wiley & Sons, Inc., 2015)
"Explore the game-changing technology that allows mobile learning to effectively reach K-12 students Mobile Learning: A Handbook for Developers, Educators and Learners provides research-based foundations for developing,evaluating, and integrating effective mobile learning pedagogy.Twenty-first century students require twenty-first century technology, and mobile devices provide new and effective ways to educate children.But with new technologies come new challenges--therefore,this handbook presents a comprehensive look at mobile learning by synthesizing relevant theories and drawing practical conclusions for developers, educators, and students.Mobile devices--in ways that the laptop, the personal computer, and netbook computers have not--present the opportunity to make learning more engaging, interactive, and available in both traditional classroom settings and informal learning environments. From theory to practice, Mobile Learning explores how mobile devices are different than their technological predecessors, makes the case for developers,teachers, and parents to invest in the technology, and illustrates the many ways in which it is innovative, exciting, and effective in educating K-12 students. Explores how mobile devices can support the needs of students Provides examples, screenshots, graphics, and visualizations to enhance the material presented in the book Provides developers with the background necessary to create the apps their audience requires Presents the case for mobile learning in and out of classrooms as early as preschool Discusses how mobile learning enables better educational opportunities for the visually impaired, students with Autism, and adult learners. If you're a school administrator, teacher, app developer, or parent, this topical book provides a theoretical, well-researched discussion of the pedagogical theory and mobile learning, as well as practical advice in setting up a mobile learning strategy"--Provided by publisher.
Machine generated contents note: Preface Acknowledgments Chapter 1: Changing Education with Mobile Learning A Brief History of Educational Technology: What will revolutionize the system? Mobile Learning: Reaching Kids Today What is Mobile Learning? Benefits and Challenges of Mobile Learning How to Make Mobile Learning Work Conclusion Notes Section 1: The Mobile Classroom Chapter 2: The Science of Learning Introduction Information Processing and Learning Other Critical Facets of Learning Implications for Mobile Learning Conclusion Notes Chapter 3: What Is It about These Devices? Connected Aware Multimodal Familiar Personal Comprehensive Consolidated Portable Relevant Secure Conclusion Notes Chapter 4: Creating the Mobile Classroom Theoretical Foundations Instructional Methods Alternative Learning Environments Conclusion Notes Chapter 5: Higher-Order Thinking Skills and Digital Fluency Higher-Order Thinking Skills Classrooms for Higher-Order Thinking Conclusion Notes Chapter 6: Instructional Management and Levels of Technology Access Mobile Learning Programs Levels of Access in the Mobile Classroom Conclusion Notes Section 2: Creating the Mobile Learning Experience Chapter 7: Mobile Technology's Defining Features Hardware Software Accessories Conclusion Notes Chapter 8: The Educational App Development Process Research Stage: Is It a Good Idea? Building the Right Team: Capturing a Variety of Expertise Building the App Case Study: App Development at SAS Curriculum Pathways Conclusion Notes Chapter 9: Design and User Experience Designing a Great App: Make It Easy Putting Great Design to Work Conclusion Notes Chapter 10: Data, Evaluation, and Learning Analytics Asking the Questions Gathering Data Mobile Data Analytics: Turning Data into Information Conclusion Notes Chapter 11: The Business of Educational Apps The Educational App Market is... How to Sell Your App: Pricing Models How Users Buy Your App Marketing Conclusion Notes Section 3: Mobile Learning for Everyone Chapter 12: Informal Learning Developing Lifelong Learners Bridging Formal and Informal Learning Conclusion Notes Chapter 13: Engaging Young Users: Apps for Preschoolers Key Skills for Preschool Apps What Makes an Engaging Preschool App? Challenges Conclusion Notes Chapter 14: Making Accessible Apps: Autism and Visual Impairment Introduction Advantages of the iPad for Special Populations Autism and Autism Spectrum Disorders (ASD) Visual Impairment Developing Accessible Apps Conclusion Notes Chapter 15: Balancing Power: Data Use, Privacy and Digital Citizenship Privacy Conclusion Notes Chapter 16: Mobile Learning Today and Tomorrow Introduction Making Mobile Learning Work The Future Conclusion Notes Appendix A: List of Apps by Chapter Appendix B: The Great App Checklist How to Use This Checklist The Great App Checklist Notes About the Authors Index .
Includes bibliographical references and index.
Keywords: Mobile communication systems in education; Educational technology